5 - Les politiques publiques agricoles face aux défis alimentaires au Niger :entre succession d’échecs et nouvelles espérances - Youssoufou, Hamadou Daouda (Africa Development, 2021)
This article tries to understand why public food policies inspired by the liberal economic and international donors have failed to halt the specter of hunger in Niger since several decades. Chronologically, the paper asks, firstly, on the credibility of national food strategies of to curb food insecurity. It shows more precisely how they eventually became ineffective, either by the lack of clear political vision, either by the ambiguous and controversial role played by food traders’ networks and international financial organizations and humanitarians. At the insistence of food crises and social and economic disasters they cause, the article questions in a second time, the opportunity of the new public “Initiative 3N” (Nigériens Nourish Nigériens) to meet the food challenges. Is it a simple nationalist slogan, to counter the popular uprisings and the pressure exerted by the international Medias, or the beginning of a hope that Nigériens will finally eradicate the horrors of hunger and food insecurity?